Investigating the Influence of Setting on Language Learning: The Case of Bahdini Kurdish Learners of English - Murad, Ivan Hasan; Al-Jumah, Khalif Abdulrahman; Othman, Hozan Gorgeen (European Scientific Journal, ESJ, 2017)
It was argued that those learning the language while mingling with the community are better learners than those learning in the academic setting where they only opt to use the academic language. The current small scale study investigates the influence of the setting on two BahdiniKurdish learners of English living in the UK in two different contexts. One of the learners has been learning English in an academic setting, while the other has been learning English through daily interactions with the community in a non-academic setting. Data were collected through interviews and observation. Results revealed that both learn English effectively for the context where their language will be used. However, the academic language learner was capable of expressing himself more than the one learning the colloquial language. The academic leaner could use a variety of strategies to express different situations and had a clearer language than the one learning the colloquial language even though the academic language learner did not mingle with academicians like the colloquial leaner did with the community.